Introduction of Panax notoginseng into pine forests significantly enhances the diversity, stochastic processes, and network complexity of nitrogen-fixing bacteria in the soil - Zhao, Xiaoyan; He, Shu; Rui, Rui; Hei, Jingying; He, Xiahong; Wang, Shu (Frontiers in Microbiology, 2025)
IntroductionNitrogen-fixing bacteria (NFB) have a pivotal impact on the nitrogen cycle within agroforestry systems. The organic management of the Panax notoginseng (sanqi)-Pinus armandii agroforestry (SPA) system resulted in nitrogen deficiency because of the lack of application of chemical fertilizers. Therefore, assessing the variability in NFB due to the cultivation of sanqi in the SPA system becomes crucial.MethodsThe seasonal dynamics in the abundance, diversity, and community structure of NFB in the soil of monocropping pine (MP) and SPA systems were assessed using real-time quantitative polymerase chain reaction and high-throughput sequencing technology.Results and discussionSanqi cultivation triggered a decrease in the abundance of NFB but increased α diversity. Additionally, significant differences in the community structure of NFB were noted between the MP and SPA systems. Moreover, the abundance of Bradyrhizobium and Azospirillum increased in the soil after sanqi was cultivated. Furthermore, the cultivation of sanqi broadened the ecological niche breadth of NFB and increased the stochasticity in its community structure assembly (i.e., dispersal limitation). Additionally, the SPA system increased the network complexity but not the stability of NFB. The structural equation model (SEM) revealed that pH directly impacted the network complexity and stability of NFB in the SPA system. Sanqi cultivation positively influences the community characteristics of NFB in the soil in the SPA system. Our study provides new insights into nitrogen cycling and utilization in the SPA system.